A Clinical Perspective on the Automated Analysis of Reflectance Confocal Microscopy in Dermatology. Issue 8 (21st January 2021) - Mehrabi, Joseph N.; Baugh, Erica G.; Fast, Alexander; Lentsch, Griffin; Balu, Mihaela; Lee, Bonnie A.; Kelly, Kristen M.
Abstract : Background and Objectives: Non‐invasive optical imaging has the potential to provide a diagnosis without the need for biopsy. One such technology is reflectance confocal microscopy (RCM), which uses low power, near‐infrared laser light to enable real‐time in vivo visualization of superficial human skin from the epidermis down to the papillary dermis. Although RCM has great potential as a diagnostic tool, there is a need for the development of reliable image analysis programs, as acquired grayscale images can be difficult and time‐consuming to visually assess. The purpose of this review is to provide a clinical perspective on the current state of artificial intelligence (AI) for the analysis and diagnostic utility of RCM imaging. Study Design/Materials and Methods: A systematic PubMed search was conducted with additional relevant literature obtained from reference lists. Results: Algorithms used for skin stratification, classification of pigmented lesions, and the quantification of photoaging were reviewed. Image segmentation, statistical methods, and machine learning techniques are among the most common methods used to analyze RCM image stacks. The poor visual contrast within RCM images and difficulty navigating image stacks were mediated by machine learning algorithms, which allowed the identification of specific skin layers. Conclusions: AI analysis of RCM images has the potential to increase the clinical utility of this emerging technology. A number of different techniques have been utilized but further refinements are necessary to allow consistent accurate assessments for diagnosis. The automated detection of skin cancers requires more development, but future applications are truly boundless, and it is compelling to envision the role that AI will have in the practice of dermatology. Lasers Surg. Med. © 2020 Wiley Periodicals LLC